(untitled) (Global Journal of Science Frontier Research, 2020)
Hibiscus sabdariffalinn (sorrel) is an annual plant belonging to the family malveceae. It has great potential and high economic value especially in the food, pharmaceutical, textile, cosmetic and paper industries. This work was designed to improve the yield and productivity of sorrel. Soil samples were collected from the University of Maiduguri Agricultural Research farm. Fertilizer treatment application and seed sowing were carried out. Weekly measurements of growth parameters including plant height, stem girth, number of leaves per plant and number of branches per plant were observed. Physicochemical composition of pre-treated soil and the chemical composition of the post-treated soils were determined by standard methods. Vitamin A contents of the calyces were determined by HPLC, Vitamin C contents of the calyces were determined by 2,6-dichloroindophenol titrimetric method, mineral contents (P, K, Na, Ca, Mg, Zn and Fe) of the calyces were determined by Atomic Absorption Spectroscopy (AAS).